Epidemiological Shifts and Transitions in the Oncological Burden in Morocco (Bangladesh Journal of Medical Science, 2026)
Background Cancer remains one of the leading causes of global morbidity and mortality, representing a critical public health challenge. This disease is defined by the uncontrolled proliferation of abnormal cells, which can invade adjacent tissues and form metastases. Objectives The primary objective of this study is to characterize the epidemiological evolution of cancer in Morocco between 2021 and 2025, using data from the National Institute of Oncology (INO). Methodology Key variables analyzed include sex, age, and tumor histological type. Statistical analysis reveals a striking rise in malignant hemopathies, whose proportion surged from less than 1% in 2021 to 20.1% in 2025, overtaking breast cancer to become the most frequently diagnosed entity. This shift coincides with a progressive masculinization of the tumor burden, with the proportion of male patients increasing from 40.78% to 42.81%. Concurrently, age distribution patterns highlight a dual dynamic: sustained predominance in the 51–69 age group alongside a concerning rise in cases among young adults aged 19–30, with 141 cases recorded in the first six months of 2025 alone. Additionally, data quality has markedly improved, evidenced by a reduction of over 50% in the rate of cases with missing information. Results These findings delineate an emerging national oncological landscape shaped by three interdependent transitions. The is characterized by the emergence of hematologic malignancies and early-onset cancers, likely driven by environmental and nutritional shifts tied to rapid urbanization. The diagnostic transition reflects institutional advancements in detection capabilities—particularly in hematologic oncology—fueled by expanded access to flow cytometry, molecular profiling, and multidisciplinary collaboration. Finally, the demographic transition manifests through the masculinization of cancer incidence and the aging profile of affected populations, mirroring broader societal changes. Conclusion Together, these trends underscore the urgent need to reorient cancer control strategies toward sex- and age-tailored interventions, while reinforcing hospital-based cancer registries as indispensable tools for evidence-based public health decision-making.BJMS, Vol. 25 No. 01 January’26 Page : 230-242